The AUDIO VISUAL MEDIA IMPLEMENTATION IN INCREASING STUDENTS' LEARNING MOTIVATION IN ISLAMIC CULTURE HISTORY LEARNING STUDENTS OF CLASS X MAN 6 JOMBANG: IMPLEMENTASI MEDIA AUDIO VISUAL DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM SISWA KELAS X MAN 6 JOMBANG - Durrotun, Munfarida; Masruroh, Laily (PAI FAI UNHASY Tebuireng Jombang, 2025)
Learning media is defined as a unit in the learning process that can support students in understanding the messages contained in the subject matter. Audio-visual media is media that emphasizes the focus of two human senses simultaneously, namely the sense of sight and the sense of hearing. One thing that needs to be considered in students in carrying out learning activities is the existence of a motivational boost to be able to achieve a goal to be achieved. This becomes the teacher's task as a motivator in presenting learning that is able to foster students' motivation when learning so that learning objectives are achieved perfectly. For SKI subject teachers at MAN 6 Jombang applying audio-visual media is as a means in an effort to increase learning motivation, therefore in this study there is a research focus, namely: 1. How is the implementation of audio-visual media in increasing students' motivation in learning SKI class X MAN 6 Jombang. 2. How is the learning motivation of students after using audio-visual media in SKI learning. 3. What are the supporting factors and inhibiting factors of audio-visual media in increasing students' learning motivation in SKI learning for class X MAN 6 Jombang students. This type of research in this study uses qualitative. In collecting data utilizing observation techniques, interviews and documentation. In conducting interviews, data were obtained from the head of the madrasah, teachers of Islamic cultural history and students. The data collected for observation and interviews were then analyzed using data source triangulation analysis techniques. Based on the results of the study it was found that: 1. The implementation of audio-visual media in an effort to increase students' motivation in learning SKI class X MAN 6 Jombang is supported by adequate facilities and infrastructure. The audio-visual media that SKI teachers use to apply is video media, which in its application goes through 3 stages: the first is to make preparations, at this stage the teacher prepares lesson plans, class preparations, the media selected and which will be applied. In the implementation stage the teacher states the objectives of learning, materials and media that are selected and will be applied. Presenting videos for the media in motivating students. And then in following up, the teacher adds material reinforcement, and determines the next step. 2. The learning motivation of students in carrying out SKI learning in class X MAN 6 Jombang indicates that students' learning enthusiasm is high, the emergence of learning enthusiasm, the emergence of student learning independence. 3. The supporting factor in implementing this media is the LCD projector facility in the media room. while the inhibiting factor is the lack of existing infrastructure in each class.